Myeloid and Mast Cell Progenitors Are Elevated in Atopic Dermatitis - Katie Ridge; Barry Moran; Mark A. Little; Cliona O’Farrelly; Jean Dunne; Julianne Clowry; Clodagh Loftus; Conor M. Finlay; Alan D. Irvine; Niall Conlon (JID Innovations)
Chronic spontaneous urticaria and atopic dermatitis (AD) are chronic skin disorders characterized by itch. Although mast cells play an integral role in the pathogenesis of chronic spontaneous urticaria, their role in AD is unclear, having a contributory role in a disease largely driven by T helper 2 polarization. Despite this, the role of mast cells in AD is important, given their release of proinflammatory mediators. Recently, myeloid and mast cell progenitors were identified as potential biomarkers for treatment response in chronic spontaneous urticaria. These Lin−CD117+CD34+FceRI+ cells appear to have increased egress from the bone marrow in atopy. We measured Lin−CD117+CD34+FceRI+ cells in the peripheral blood of 10 individuals with AD and 10 healthy controls. Flow cytometry revealed a significant increase in myeloid progenitors in participants with AD (P = .0067). Total serum IgE levels did not correlate with myeloid progenitors. To our knowledge, examination of this cell type in AD is previously unreported. Our findings suggest increased progenitor egress from the bone marrow in these patients and a possible role for myeloid progenitors in disease pathogenesis.